Analisis Ketrampilan Menulis Karangan Sederhana Peserta Didik Kelas III SD Negeri Klampok 06 - Muqiema Sholati; Laelia Nurpratiwiningsih; Didik Tri Setiyoko (Peneliti.net, 2022)
Writing skill is a very complex language activity, because at the time of writing it must involve various cognitive activities and certain skills in a process of producing a written text that contains selected ideas, information, facts, and other things as a person's mindset. is to describe the analysis of simple essay writing skills for third grade students of SD Negeri Klampok 06, grade III of SD Negeri Klampok 06 in the academic year 2022/2023. This study uses qualitative research with data collection techniques of observation and documentation. The validity of the data is done by triangulation, namely by checking data from various data sources that already exist in various ways. The data analysis technique used is data reduction, data presentation and conclusion drawing. The population and samples used in this study were teachers and students. Based on the results of the study, it can be concluded that: the writing skills of students are able to write well, understand punctuation marks, understand capital letters and ordinary letters although there are some students who still do not know it.